CoCr7C3-like nanorods embedded on carbon nanofibers as effective electrocatalyst for methanol electro-oxidation. (24th May 2018) - Al-Enizi, Abdullah M.; Brooks, Robert M.; El-Halwany, M.M.; Yousef, Ayman; Nafady, Ayman; Hameed, R.M. Abdel
Abstract: CoCr7 C3 -like nanorods encapsulated in carbon nanofibers shell [CoCr7 C3 -CNFs] were prepared using a simple electrospinning technique. The as-prepared nanocomposite was physically characterized using XRD, SEM, TEM and EDX analysis techniques. The electrocatalytic activity of CoCr7 C3 -CNFs was examined for methanol electro-oxidation in alkaline medium using cyclic voltammetry and chronoamperometry. The fabricated CoCr7 C3 -CNFs revealed good electroactivity towards methanol oxidation reaction. The measured low onset potential value [−80 mV (Ag/AgCl)] implied a marked enhancement in the oxidation kinetics at CoCr7 C3 -CNFs surface. Chronoamperometry test also displayed an increased steady state oxidation current density value of 18.42 mA cm −2 at 400 mV after 1800 s. This synthesized low cost, highly active and stable nanocomposite could be widely employed as a promising anode material in direct methanol fuel cells. Highlights: CoCr7 C3 -Like NRs Embedded on CNFs are introduced. CoCr7 C3 NRs Embedded on CNFs was synthesized by simple and effective technique. Co enhances the formation of Cr7 C3 at low temperature. Due to carbon shelling, the introduced composite is chemically stable. Nanocomposite showed good electrocatalytic activity in the methanol fuel cells.